Whole genome sequencing and methylome analysis of the wild guinea pig - Weyrich, Alexandra (BMC Genomics, 2014)
BACKGROUND: DNA methylation is a heritable mechanism that acts in response to environmental changes, lifestyle and diseases by influencing gene expression in eukaryotes. Epigenetic studies of wild organisms are mandatory to understand their role in e.g. adaptational processes in the great variety of ecological niches. However, strategies to address those questions on a methylome scale are widely missing. In this study we present such a strategy and describe a whole genome sequence and methylome analysis of the wild guinea pig. RESULTS: We generated a full Wild guinea pig (Cavia aperea) genome sequence with enhanced coverage of methylated regions, benefiting from the available sequence of the domesticated relative Cavia porcellus. This new genome sequence was then used as reference to map the sequence reads of bisulfite treated Wild guinea pig sequencing libraries to investigate DNA-methylation patterns at nucleotide-specific level, by using our here described method, named ‘DNA-enrichment-bisulfite-sequencing’ (MEBS). The results achieved using MEBS matched those of standard methods in other mammalian model species. The technique is cost efficient, and incorporates both methylation enrichment results and a nucleotide-specific resolution even without a whole genome sequence available. Thus MEBS can be easily applied to extend methylation enrichment studies to a nucleotide-specific level. CONCLUSIONS: The approach is suited to study methylomes of not yet sequenced mammals at single nucleotide resolution. The strategy is transferable to other mammalian species by applying the nuclear genome sequence of a close relative. It is therefore of interest for studies on a variety of wild species trying to answer evolutionary, adaptational, ecological or medical questions by epigenetic mechanisms. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-1036) contains supplementary material, which is available to authorized users.